How to prepare students for standardized tests - Powell, Sara Davis; Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2001)
This is a videotape that explores several steps teachers can take to help students prepare for these tests. Classroom teachers give tips on A. How to integrate test preparation into effective daily instruction. B. How to auqment students' vocabulary and editing skills. C. How to help students become effective problem-solvers. D. How to increase students' test-taking skills and abilities
Title from title screen
Narration: Sara Davil Powell
Keywords: Teachers -- Training of; Test-taking skills; Educational tests and measurements; Achievement tests